(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article discusses the importance of a variative education approach in developing the professional competence of specialists working in the field of physical education and sports. It also analyzes issues related to improving specialists’ knowledge, skills, and abilities through democratization, liberalization, and the application of innovative technologies within the professional development system. The study identifies ways to increase the effectiveness of professional development processes through the use of modern pedagogical technologies, distance learning forms, and interactive teaching methods.